Geogrid creep and tensile tests performed with nonconventional equipment - França, F. A.N.; Massimino, B. M. [UNESP]; Silva, J. O. [UNESP]; Iceri, F. Y. [UNESP]; Zornberg, J. G. (My University, 2014)
Creep behavior of geosynthetics is commonly determined by means of creep tests performed with in-isolation specimens. Soil-geosynthetic interaction and duration of the tests were already addressed in previous studies with nonconventional conditions tests. However, since the applied load level in creep tests is referred as a percentage of the geosynthetic tensile strength computed from short-term tests, it is necessary to create a procedure to reproduce the same nonconventional conditions in tensile tests. Thus, this paper presents the improvement of the equipment developed to perform nonconventional creep tests in order to make it capable of conducting nonconventional tensile tests. The main adjustments regarded the loading system and the specimen elongation measurement system with video camera. A biaxial geogrid was used in preliminary tensile tests to verify the equipment performance. Results obtained with the new equipment were quite similar to those from standard apparatus. However, further improvements are still necessary, mainly regarding the specimen elongation measurement system.
Keywords: Confined-accelerated conditions; Geosynthetics; Tensile strength